2005
DOI: 10.1063/1.1928316
|View full text |Cite
|
Sign up to set email alerts
|

Outdiffusion of La and Al from amorphous LaAlO3 in direct contact with Si (001)

Abstract: We have evaluated the thermal stability of Al2O3/LaAlO3/Si (001) stacks with atomic force microscopy, x-ray diffraction, transmission electron microscopy, and secondary ion mass spectrometry using a back side polishing approach. Crystallization of the amorphous LaAlO3 film was found to occur for rapid thermal anneals (RTA) above 935 °C for 20 s, in flowing N2. Penetration of Al and La into the underlying Si (001) is clearly observed for RTA at or above 950 °C for 20 s in flowing N2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
44
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 18 publications
4
44
0
Order By: Relevance
“…However, HfO 2 layers on Si tend to possess a SiO 2 -based interfacial layer which limits the attainment of very low effective oxide thickness (EOT). Future scaling calls for lower EOTs, and for this a leading candidate is LaAlO 3 [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, HfO 2 layers on Si tend to possess a SiO 2 -based interfacial layer which limits the attainment of very low effective oxide thickness (EOT). Future scaling calls for lower EOTs, and for this a leading candidate is LaAlO 3 [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…But a key advantage of LaAlO 3 is that it has much lower atomic diffusion rates than HfO 2 , which limits the growth of any subcutaneous SiO 2 layer between the Si channel and the oxide [12][13][14]. Recently amorphous LaAlO 3 gate stacks with an EOT of only 0.3 nm were achieved [15].…”
Section: Introductionmentioning
confidence: 99%
“…The MBD growths on hydrogen-terminated ͑100͒ Si surfaces were carried out at temperatures Ͻ100°C. 5,7 Importantly, the previous physical analysis of the samples indicated that, even after transfer in the room ambient, they have less than 0.02 nm ͑less than 0.1 ML͒ of Si oxide at the interface, i.e., the metal oxide is in direct contact with Si at least on 90% of the interface area. 5 Some of the samples received an additional 10 min anneal at 650 or 800°C in N 2 +5% O 2 to remove H from the interface and allow atomic interactions between Si, the oxide, and the supplied oxygen.…”
mentioning
confidence: 96%
“…5 Some of the samples received an additional 10 min anneal at 650 or 800°C in N 2 +5% O 2 to remove H from the interface and allow atomic interactions between Si, the oxide, and the supplied oxygen. 7 In contrast, the PLD oxides were grown on chemically oxidized ͑100͒ Si resulting in a ϳ1-nm-thick silicon oxide IL ͑Fig. 1 in Ref.…”
mentioning
confidence: 99%
“…[10][11][12][13][14] Critically, LaAlO 3 has much lower atomic diffusion rates and less tendency to form the SiO 2 -based interfacial layer during processing. 15,16 Recently, amorphous LaAlO 3 gate stacks with an EOT of 0.3 nm have been achieved. 17 Crystalline LaAlO 3 ͑100͒ is lattice matched to Si͑100͒, with a 45°lattice rotation, and it could grow as an epitaxial oxide.…”
mentioning
confidence: 99%